Allele frequencies of Bordetella pertussis virulence-associated genes identified from pediatric patients with severe respiratory infections. Issue 7 (July 2020) - Imamura, Tadatsugu; Shoji, Kensuke; Kono, Naoko; Kubota, Mitsuru; Nishimura, Nao; Ishiguro, Akira; Miyairi, Isao
Abstract: Bordetella pertussis ( B. pertussis ) infection occasionally causes severe respiratory infections in children. Potential association between virulence-associated gene alleles and severe clinical outcomes has been suggested; however, frequencies of these alleles in pediatric patients with severe pertussis have not been clarified. We retrospectively tested stored respiratory samples collected from B. pertussis -positive patients by polymerase chain reaction targeting for major virulence-associated genes; fimbrae ( fim ) serotype 3 ( fim3 ), pertactin ( prn ), pertussis toxin A ( ptxA ), and pertussis toxin promotor ( ptxP ). Based on the identified sequences, multilocus sequence typing (MLST) was conducted. Association of gene allele frequency and clinical outcomes such as management in pediatric intensive care unit, intubation, and mortality was analyzed. Out of 25 patients with available samples, the most prevalent allele for each virulence-associated gene was fim3A (17/21, 83%), ptxA1 (20/23, 87%), prn2 (13/16, 81%), and ptxP3 (14/17, 82%). In the study, total of 3 MLST types were identified; MLST-1 from 3 patients (19%), MLST-2 from 10 patients (63%), and MLST-4 from 3 patients (19%). Detection rate of the major MLST type; MLST-2 was significantly higher for patients who required intubation compared to those who did not (6/6, 100% vs 4/10, 40%; p = 0.034). In conclusion, MLST-2 was the most common MLST type in B. pertussis isolated from Japanese children with severe pertussis. Further studies investigating its causal association with disease severity is warranted.